Frequency of canine skin tumors histopathology diagnosed in the Veterinary Pathology Laboratory of Universidad Nacional Mayor de San Marcos (1999-2012) - Medina, Isabel (2017)
The aim of the present study was to determine the frequency of skin neoplasms in dogs in the Lima Metropolitan area, based on a retrospective analysis of the diagnostic work carried out in the Laboratory of Veterinary Pathology of the Universidad Nacional Mayor de San Marcos, Lima, Peru. Histopathological reports of canine neoplasms from January 2, 1999 until December 21, 2012 were reviewed (n=789). Malignant neoplasms represented 62.5% of the total skin neoplasms. Among the malign and benign epithelial neoplasms, the squamous cell carcinoma (50.0%, 72/147) and papilloma (26.8%, 33/123) were the most frequent respectively. In the case of malignant and benign mesenchymal neoplasms, mastocytoma (23.7%, 70/295) and cutaneous extramedullary plasmacytoma (39.5%, 68/172) were the most prevalent, respectively.